Constructing Marx in the history of ideas*. Issue 1 (4th May 2017) - Ghosh, Peter
ABSTRACT: Publication of a new general biography of Marx is a reminder that no intellectual biography exists. This is an extraordinary omission, and the present article offers a draft outline of such a biography. Some central elements from established twentieth-century views of Marx are reviewed and upheld, such as the centrality of his early ideas before 1848 and the essential unity of his thought overall. Yet there are also substantial revisions and clarifications: the supreme importance of labour (rather than alienated labour); the revised status of the 'German Ideology'; the mistaken neglect of the Poverty of Philosophy ; Marx's identity as a synthetic and universalist thinker. More important than any particular finding is the underlying analytical standpoint. Marx is treated as a historical subject like any other. He is removed from the partial isolation created by political constraint or embarrassment, and located unreservedly within the broad stream of the history of ideas, a stream which is continuous with the present. In this history, Marx and his Western European reception are two of the greatest subjects.